2013
DOI: 10.1007/s11934-013-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Aneurysms

Abstract: A renal artery aneurysm is defined as a dilated segment of renal artery that exceeds twice the diameter of a normal renal artery. Although rare, the diagnosis and incidence of this entity have been steadily increasing due to the routine use of cross-sectional imaging. In certain cases, renal artery aneurysms may be clinically important and potentially lethal. However, knowledge of their occurrence, their natural history, and their prognosis with or without treatment is still limited. This article aims to revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 43 publications
2
85
0
1
Order By: Relevance
“…Historically, autopsy indicated an RAA incidence rate of about 0.03% to 0.09%, but the use of angiography and computed tomography (CT) angiogram (Figure 2) has led to increased detection, which raises the estimated incidence rate to 1% (1,2). Hypertension is the most common presenting symptom (up to 90%) (1, 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, autopsy indicated an RAA incidence rate of about 0.03% to 0.09%, but the use of angiography and computed tomography (CT) angiogram (Figure 2) has led to increased detection, which raises the estimated incidence rate to 1% (1,2). Hypertension is the most common presenting symptom (up to 90%) (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Rundback et al classifi ed RAA into three categories (Figure 3) (2). Saccular aneurysms arising from the main renal artery or the large segmental branch are amendable to an endovascular approach and are classifi ed as type 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have suggested that asymptomatic RAAs with a size of <1.5 cm and circumferential calcifications possess a low risk for rupture. 4) In contrast, non-calcified saccular aneurysms that are accompanied with hypertension have a high risk for rupture (>20%). Likewise, the risk for rupture is high in pregnant patients, especially during the third trimester, and is associated with a maternal mortality of approximately 50% and a fetal mortality of approximately 80%.…”
Section: Discussionmentioning
confidence: 99%
“…4) Nevertheless, a careful selection of patients is mandatory as complications such as the intraoperative rupture of the RAA may result in the loss of the kidney or even the death of the patient.…”
Section: Discussionmentioning
confidence: 99%